Bilateral laminotomy through a unilateral approach (minimally invasive) versus open laminectomy for lumbar spinal stenosis. (4th March 2021) - Horan, Jack; Husien, Mohammed Ben; Bolger, Ciaran
Abstract: Purpose: To compare the outcomes of minimally invasive (MI) bilateral laminotomy via unilateral approach versus open laminectomy in the treatment of lumbar spinal stenosis (LSS). Materials and Methods: In this prospective study, 62 patients were treated for LSS and were assigned to one of two groups over a 6-month period. Group A comprised 37 patients that underwent MI bilateral laminotomy. Group B comprised 25 patients that underwent open laminectomy. Follow-up duration was 3 years. The primary outcomes were the visual analogue scale (VAS) pain outcome score for back and leg, the Oswestry Disability Index (ODI) and complications. Results: MI methods were superior in most primary outcomes compared to open laminectomy. VAS back pain outcome was reduced from close to 7 to 4 in both groups. VAS leg pain was reduced from 6.8 to 3.2 in MI group and from 8.7 to 3.5 in the open group ( p  > 0.05 between groups, p  < 0.05 comparing pre- to post-operative back and leg pain). ODI improved from 56.5 to 13 and 58 to 24 in MI and open groups, respectively ( p  > 0.05 between groups, p  < 0.05 comparing pre- to post-operative disability). Complication and revision rates were lower in the MI technique than open laminectomy (8 versus 56%, p  < 0.05; 3 versus 12%, p  > 0.05). Length of stay ranges were less in MI than open group (1–3 versus 7–30 days, p  > 0.05). Conclusions: Bilateral laminotomy through a unilateral approach (minimally invasive) and open laminectomy are both effective in improving pain and disability in LSS. MI procedures have an advantage in shorter hospital stays, sparing of more bony structures and lower complication rates. MI unilateral decompression is at least as good as laminectomy in the treatment of LSS.